Substrates for Packaging of Silicon Carbide Power Electronics - Ruppi, Robert (My University, 2011)
Silicon based power semiconductor devices are the fundamental components of electronic systems and circuits today. The need for high voltage devices that can operate at high ambient temperatures and switching speeds are growing; especially for the military, automotive and aerospace industries. Si based power electronics dominate the current market. However, Si suffers from limitations such as low band gap and low thermal conductivity, leading to limitations in switching speeds, blocking voltages and operating temperatures. Due to these limitations, there is an increasing interest in wide band gap semiconductor materials such as silicon carbide (SiC) and gallium nitride (GaN). To meet the future demands of high power and high temperature components based on wide band gap semiconductors, new packaging concepts are also required. Materials such as aluminium nitride (AlN) and alumina (Al2O3) are appropriate for high power packaging, due to their high thermal conductivity and superior mechanical stability. In this master thesis project I have evaluated a new packaging concept for power electronics based on substrates of Al2O3 and AlN. A method to deposit nano silver ink by ink jet printing directly on Al2O3 is developed and the nano silver ink performance has been evaluated. It is shown that parameters like surface preparation and sintering conditions are essential for the final result. The resistivity of the printed ink is evaluated and results indicate that the resistivity is close to bulk silver. Experiments show that the nano silver can be sintered at temperatures as low as 250 °C to achieve sufficient electrical conductivity. Further, a packaging concept based on existing substrate technology (Direct Bonded Copper (DBC) with AlN core) is designed, simulated and manufactured by conventional etching technology.
Keywords: Packaging, silicon carbide, SiC power electronics, printed electronics, substrates for power electronics